Pengujian Kinerja Bluetooth Wireless Exposure Switch untuk X-ray Mobile Unit - Sulistiyadi, Akhmad Haris; Rochmayanti, Dwi; Wibowo, Ardi Soesilo (Poltekkes Kemenkes Semarang, 2026)
Background: Radiation exposure to radiographers in on-site X-ray mobile examination is relatively high due to lack of shielding. Bluetooth wireless exposure system was developed to overcome the situation by providing longer range of exposure distance. The system combines the exposure trigerring componnents, Bluetooth moduls, and microcontrollers. The aim of this study was to analyze the performance of the developed Bluetooth Wireless Exposure Switch for X-ray mobile unit. Methods: This is quantitative research with an explorative approach. The system was installed on CorsixTM mobile X-ray in clinical set up. The X-ray output was tested refering to modified protocol for kVp output, timer accuracy, and radiation reproducibility. Performance was assessed by comparing the X-ray output triggerred by the wireless exposure switch and conventional original wired exposure switch. The response time of the wireless system was measured the delay between transmiting and receiving time using software provided by ArduinoTM. Results: There were no difference on kVp output (p value >0.05), timer accuracy (p value >0.05), and radiation reproducibility (p value >0.05) between exposure trigerring using Bluetooth wireless exposure switch and the conventional switch. The time delay between transmiting and receiving time were 0,0612 second for pre-exposure phase and 0,0736 for exposure phase. Conclusions: Bluetooth wireless exposure switch showed a good performance in trigerring X-ray exposure and feasibly applied in clinical practice.